All parties?: illegal parties and the 1977 elections - Senent Sansegundo, Juan Carlos (Hispania Nova, 2021)
The 1977 elections were the first democratic elections to be held in Spain since February 1936. But in them, not all political parties were legal. We try to answer to some questions that we have asked ourselves: Why were they not legalized? What political parties is it about? Couldn`t they stand for the elections? We delve into this question, which has not been dealt with in specialized historiography and which represents an anomalous situation in the process of political change that was taking place in those years in Spain, though, above all, newspaper sources, although also from archives and with the consultation of the necessary bibliography, to answer the questions raised.